Sentidos da docência para egressos das licenciaturas a distância da Universidade Federal do Espírito Santo no Polo de Itapemirim – Espírito Santo - Sales, Silvana Batista (2014)
Investigate the meanings of being and knowledge of teachers with emphasis on initial training of teachers for basic education through distance education mode - EAD. Questions the ways in which being a teacher and the teaching profession knowledge were formed along the learning paths traveled by students graduating from the first three degree courses in Chemistry, Physics and Visual Arts, offered by the Federal University of Espírito Santo (Ufes) under the System Open University of Brazil - UAB, between 2008 and 2014, the Polo city Itapemirim / ES, in a time frame defined as before, during and after the payment of such courses. Presupposes a critical theoretical perspective, which includes the training and teaching as historical processes of social and collective construction, which do not have start and end in itself, for itself and for itself. The research is outlined as a qualitative case study. The approach to the subject was given by techniques aimed at collecting descriptive data, using three main tools in semi-structured format: a questionnaire, a press conference and a thematic virtual forum. To compose the directory of data, there were also information resulting documents and legal bases that support the provision of courses as well as the monitoring reports and managed. Data analysis was done through the triangulation technique, with theoretical support in studies of Freire, Nóvoa and Tardif. Highlights the need for studies in articulated training to EAD, as well as consideration of the teaching of everyday knowledge in policy proposition to its formation. Reveals a variety of meanings attributed to the teaching of concepts and teacher knowledge and its incorporation in the midst of training processes throughout the life of the subject. Recognizes the need for continuous training of teaching after obtaining their professional qualification and points out the EAD as a possibility of access to such training in / by the public University in times and spaces that have been constituted, in the midst of new information technologies and communication. Emphasizes the importance of the UAB System for the dissemination of training and distance learning, as well as the need for institutionalization of this modality as a way of overcoming the emergency and provisional nature of the current teacher training policy in Brazil.